(untitled) (Bulletin KNOB, 1999)
The imposing hospital chapel of the former St Elisabeths Gasthuis in Arnhem was built in two phases. The substructure in neorenaissance style was realized in 1897. The domed funeral parlour was situated there. It was not until 1904-1906 that the neogothic chapel was built. The difficult process of its construction was related to the high costs and financial problems due to which archiepiscopal consent was not forthcoming. The place of worship was built after the design of the Arnhem architect J.W. Boerbooms (1849-1899). Because of his premature death the object was completed by architect W.G. Welsing (1858-1942), also from Arnhem. He held on to his predecessor’s drawings Looking at the design of the chapel it may be concluded that there are various similarities to specific medieval church buildings, notably the Skt. Elisabethkirche in Marburg. Both in Arnhem and in Marburg it concerns hall-churches with savories above the side aisles and double rows of windows on top of each other. In both cases there is a trefoil-plan choir. The situation of a funeral parlour underneath the Arnhem choir, in combination with the trefoil shape, appeals to the symbolical reference to the grave of Christ. Besides, there is a link with the funeral function of the church in Marburg, where the relics of St Elisabeth of Thoringen are to be found. It was this saint who was an inspiring example for the nuns attending to the Arnhem hospital. The aspects mentioned lead to the assumption that the Arnhem hospital chapel was built from the commissioner’s need to give powerful expression to the significance of St Elisabeth. It is most likely that in preparing the design Boerbooms particularly looked at the Marburg church referred to, besides using other examples. Thus he created a place of worship that was more than just a simple hospital chapel and through which the spiritual background of the St Elisabeths Gasthuis could be given concrete expression.